Modelling the contribution of CO2 emissions from fuel used on total CO2 emissions at power generation in Indonesia - Hafizan, J.; Mustafa, M.; Budiono, R.; Sukono, .; Supian, S.; Nurzaman, M. (2019)
For electricity production, humans use fossil fuels, such as coal, fuel oil, diesel oil, and gas. The use of these fuels is a major source of greenhouse gas emissions, especially carbon dioxide (CO ) gases. In this paper, we have proposed the model of CO emissions from the fuel used to total CO , in electricity production in Indonesia. Modelling is done by using multiple linear regression, while the parameter estimation is done by using ordinary least square method (OLS). The data used are CO emissions in million tonnes of greenhouse gas generations for the period of 2000-2015. Based on the results of the analysis, it can be seen that the contribution of CO emissions from the fuel used, to total CO emissions in electricity production significantly follows the multiple linear regression model. The total of CO emission prediction by using estimated model estimator, yields mean absolute error (MAPE) of 0.01026323. These concludes that the prediction data is very close to the actual data.